Fitness activities from the lens of physical education teachers: Pursuing mental health and balancing act in stressful work environment - Jesus O. Tubog, Jr. (Environment and Social Psychology, 2025)
This exploratory study examined the role of fitness activities in enhancing mental health among Physical Education (PE) teachers in Zamboanga, Philippines, focusing on their experiences managing stress in demanding work environments. Semi-structured interviews were conducted with 40 PE teachers to explore their preferred fitness routines, the impact of exercise on their mental clarity and stress management, and the consequences of skipping workouts. The data were analyzed using a structured thematic analysis approach, drawing from established qualitative frameworks to ensure rigor and credibility. Findings showed that PE teachers prioritize quick, space-friendly exercises such as deep breathing, stretching, and light cardio for immediate stress relief, while high-energy activities like Zumba and circuit training were favored for mood elevation and social engagement. Participants consistently reported improved mental clarity, patience, and positivity after engaging in fitness activities, whereas skipping workouts resulted in heightened stress, irritability, and reduced emotional balance. Overall, the study underscores the importance of integrating fitness routines into the daily lives of PE teachers as a critical form of self-care and stress management, ultimately enhancing their mental well-being and resilience in navigating the demands of their profession.